Trace elements in phases of the Sikhote-Alin iron meteorite - Weinke,Helmut H.; Kiesl,Wolfgang; Kluger,Friedrich; Koeberl,Christian; Espen,Piet Van (1986)
P(論文) A sample of the IIAB iron meteorite Sikhote-Alin has been studied for trace elements in the metal and troilite phases using electron microprobe analysis, radiochemical neutron activation analysis, and secondary ion mass spectrometry. Comparison with other members of the IIAB iron group shows that this is a typical IIAB meteorite, and fits quite well in the group, which shows a wide variations of the content of some trace elements. The variation and also the distribution coefficients of some trace elements between metal and sulphide is not consistent with a simple fractional crystallization model. departmental bulletin paper